2008
DOI: 10.1016/j.rasd.2007.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Colored overlays enhance visual perceptual performance in children with autism spectrum disorders

Abstract: Children with Autism Spectrum Disorders (ASD), together with controls matched for age and ability participated in three experiments that assessed the therapeutic benefit of colored overlays. The findings from the first experiment showed that a significantly greater proportion of children with ASD, than controls, increased reading speed when using a colored overlay. This finding was replicated in the second experiment which also showed that therapeutic benefits were only observed when participants were instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 42 publications
4
34
0
1
Order By: Relevance
“…Other studies (Ludlow et al, 2006, 2008, 2012) found, in clinical settings, a perceptual benefit from the use of colored filters in a large proportion of individuals with ASD. The overlays were designed to sample chromaticity systematically and comprehensively so that if there was any color that was beneficial, there was an available overlay or combination of overlays providing a close approximation to this color.…”
Section: Introductionmentioning
confidence: 91%
“…Other studies (Ludlow et al, 2006, 2008, 2012) found, in clinical settings, a perceptual benefit from the use of colored filters in a large proportion of individuals with ASD. The overlays were designed to sample chromaticity systematically and comprehensively so that if there was any color that was beneficial, there was an available overlay or combination of overlays providing a close approximation to this color.…”
Section: Introductionmentioning
confidence: 91%
“…Dry erase boards or gel pens offer a harder and smoother writing experience with less drag, whereas fine point pens and thicker papers may offer more resistance when writing. Finally, individuals with autism may also not only have tactile and kinesthetic sensitivities, but some also have visual sensitivities to the paper and text color (Ludlow et al 2008). Color screens tests may be useful in determining which colors are more effective in supporting the writing needs for a specific student (Wizla 2012).…”
Section: Sensory At Feature Accommodationsmentioning
confidence: 99%
“…The student will start by choosing a colored overlay based on the process Ludlow et al (2008) used in the first experiment of their study. Students will be asked to look at text through two colored overlays side by side and determine which color provides the clearest view.…”
Section: Methods Of Proceduresmentioning
confidence: 99%
“…Many studies (Northway et al, 2010;Dain, Floyd & Elliot, 2008;Ludlow et al, 2008;Trout et al, 2007;Carbo, 2010) have been conducted and suggest that the use of colored overlays increases the reading fluency of students with a variety of disabilities. Students with ADHD, Autism Spectrum Disorders, Specific Reading Disorders, and those considered at risk have participated in studies involving colored overlays.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation